2012
DOI: 10.1186/scrt109
|View full text |Cite
|
Sign up to set email alerts
|

The secretome of stem cells isolated from the adipose tissue and Wharton jelly acts differently on central nervous system derived cell populations

Abstract: IntroductionIt is hypothesized that administration of stromal/stem cells isolated from the adipose tissue (ASCs) and umbilical cord (HUCPVCs) can ameliorate the injured central nervous system (CNS). It is still not clear, however, whether they have similar or opposite effects on primary cultures of neuronal populations. The objective of the present work was to determine if ASCs and HUCPVCs preferentially act, or not, on specific cell populations within the CNS.MethodsPrimary cultures of hippocampal neurons wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(93 citation statements)
references
References 23 publications
6
86
0
1
Order By: Relevance
“…For instance, Ribeiro et al previously reported that the secretome of bmMSCs increased the cell viability of hippocampal cultures as well as the number of neurons in culture [26]. Moreover, similar results were obtained using the conditioned medium of HUCPVCs and ASCs in neuronal and glial cultures [27,28]. To the best of our knowledge, the results presented here show for the first time the secretome interactions between OECs and ASCs, HUCPVCs, and bmMSCs on the metabolic activity and proliferation of the cells.…”
Section: Discussionsupporting
confidence: 70%
“…For instance, Ribeiro et al previously reported that the secretome of bmMSCs increased the cell viability of hippocampal cultures as well as the number of neurons in culture [26]. Moreover, similar results were obtained using the conditioned medium of HUCPVCs and ASCs in neuronal and glial cultures [27,28]. To the best of our knowledge, the results presented here show for the first time the secretome interactions between OECs and ASCs, HUCPVCs, and bmMSCs on the metabolic activity and proliferation of the cells.…”
Section: Discussionsupporting
confidence: 70%
“…Several studies have demonstrated that ASCs are able to efficiently differentiate toward adipogenic-chondrogenic-neurogenic-osteogenic-like cells (Quirici et al, 2010;Choudhery et al, 2013), and to modulate biomolecular signals (Gonzalez-Rey et al, 2010;Sacerdote et al, 2013;Nasef et al, 2008;Yoo et al, 2009). In particular, vascular endothelial growth factor (VEGF), epidermal growth factor (EGF) and the transforming growth factor-beta 1 (TGF-b1) belong to the stem cell secretome (Ribeiro et al, 2012;Salgado et al, 2010) and these growth factors have been related to pain modulation and neuroprotection (Kiguchi et al, 2014;Maiese, 2015;Wang et al, 2015).…”
mentioning
confidence: 99%
“…Proteomic analysis of AD-MSCs secretome revealed a high content of anti-inflammatory mediators including transforming growth factor (TGF)-β, prostaglandin E2 (PGE2), and IL-10. AD-MSCs also show angiogenic properties, with recent evidence of a potential role in healing damaged tissue through secretion of vascular endothelial growth factor such as vascular endothelial growth factor (VEGF), HGF, IGF-1, platelet-derived growth factor-BB (PDGF-BB), and angiopoietin-like 4 protein (Locke et al 2009;Salgado et al 2010;Ribeiro et al 2012;Kalinina et al 2015).…”
Section: Adipose-derived Mscsmentioning
confidence: 99%